Does childhood chorea mean sydenham chorea everytime? - Ozgor, Bilge; Ince , Damla; Gungor, Serdal; Karakurt, Cemsit (Annals of Medical Research, 2022)
Aim: We were retrospectively our experience in Sydenham Chorea and reexamined 39 patients with choreiform movement disorder who were admitted to pediatric neurology and cardiology outpatient clinics between 2010 and 2017.Materials and Methods: We reviewed these case symptoms, diagnosis period, differential diagnosis and shortening the duration of symptoms with chorea treatment.Results: Two of 39 patients who diagnosed Sydenham Chorea, were finally diagnosed Systemic Lupus Erythematosus. Symptoms duration time is shorter with neurodol or valproaic treatments.Conclusion: Although Sydenham Chorea’s is the most common movement disorders, the practitioners should aware of the differential diagnosis. The relapse of Acute Rheumatic Fever with chorea can be prevented by administering antibiotic prophylaxis.
Keywords: Chorea; lupus; carditis